Prispevek k poznavanju favne listnih uši (Sternorrhyncha: Aphididae) Slovenije - Modic, Špela (Acta entomologica slovenica (Ljubljana), 2008)
The current paper is a synthesis of the knowledge of Aphids in the Slovenian fauna (Sternorrhyncha: Aphididae) and presents the results of research on flight dynamics of aphids in the period of 2003-2006 when we monitored systematically in the four areas of potato seed production: Komenda, Jablje, Šentvid pri Stični and Libeliče. During the potato vegetation yellow water (Moerick) traps were used to determine the presence of aphids and to identify the species. The majority of aphids of the family Aphididae that were caught belong to the genus Aphis. In the samples some species new to the Slovene fauna were discovered: Aphis spiraecola Patch, Amphorophora gei (Börner), Chaitophorus leucomelas Koch, Chaitophorus populeti (Panzer), Drepanosiphum aceris Koch, Cinara sp., Macrosiphum cholodkovskyi (Mordvilko), Macrosiphum gei (Koch), Myzocallis castanicola Baker, Myzocallis coryli (Goeze), Protrama flavescens (Koch), Protrama ranunculi del Guercio, Rhopalosiphum maidis (Fitch), Thelaxes dryophila (Schrank), Therioaphis luteola (Börner), Trama rara Mordvilko and Tuberolachnus salignus (Gmelin). On the basis of the previous publications it was established that 180 species of true aphids of the family Aphididae were known in Slovenia. With our contribution, the numberis 197 now.
Keywords: entomologija; favna; listne uši; Slovenia; Slovenija; varstvo rastlin